Low Glutathione Peroxidase Plasma Levels Related to the Severity Degree of Vitiligo - I Gusti Ayu Agung Praharsini (Journal of Global Pharma Technology, 2019)
Introduction: Vitiligo is a pigmentation disorder caused by damage to melanocytes which causes loss of pigment production on the skin and mucosal surfaces. The etiology of vitiligo is still unknown, but there are several theories regarding the occurrence of damage and death of melanocytes in vitiligo. One is a widely known theory is the theory of oxidative stress. The body has a defence mechanism against free radicals through the formation of antioxidants, one of which is glutathione peroxidase (GPx). Increased free radicals will result in decreased levels of glutathione peroxidase. This study aims to prove the correlation between plasma glutathione peroxidase and an increase in the severity of vitiligo. Method: The study design using an analytical study with a cross-sectional approach in vitiligo patients at Sanglah Hospital Denpasar. Sampling were done with consecutive sampling technique involving 40 vitiligo patients and 20 non-vitiligo controls that met the inclusion and exclusion criteria. Venous blood sampling was performed to measure GPx plasma levels and physical examination to measure the severity of vitiligo based on VASI scores. The collected data were analysed using SPSS version 23.0 with normality test, unpaired T test, correlation test and chi-square to get the prevalence ratio (PR).Result: The results showed a lower level of GPx plasma in vitiligo patients (72.3 ± 82.5 ng/mL) compared to non-vitiligo (160.63 ± 124.33 ng/mL) subjects (p<0.05), low GPx levels were a risk factor for vitiligo with a prevalence ratio (PR 1.57; CI 95% = 1.89-2.776; p<0.05) and plasma GPx levels have a strong negative correlation with the degree of vitiligo severity based on vitiligo area severity index (VASI) scores in vitiligo subjects (r=-0.60; p <0.05) Conclusions in this study there is a negative correlation between plasma GPx levels with vitiligo severity and low GPx levels are risk factors for vitiligo.Keywords: Glutathione peroxidase, Vitiligo, Vasi score.